ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENGHAFALKAN PERKALIAN PADA SISWA KELAS IV SEKOLAH DASAR - Shavina Ananda Chairani; Chrisnaji Banindra Yudha; Indah Wardatussa’idah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the need for developing interactive learning media to improve multiplication memorization skills among fourth-grade elementary students. The issue addressed is the students’ low mastery of multiplication, particularly with higher numbers, and the lack of effectiveness in conventional teaching methods. The research employed a descriptive quantitative approach with data collection techniques including closed questionnaires for 17 students of Class IV-C and open interviews with the homeroom teacher. The findings indicate that most students experience progressive difficulty in memorizing multiplication and express a strong preference for fun and interactive learning. Meanwhile, the teacher acknowledged the limitations of current methods and highlighted the need for innovative media tailored to students' learning styles. These results underscore the urgent need to develop interactive learning tools that enhance student engagement, simplify abstract concepts, and support gradual and sustained multiplication memorization.